MHD Heat and Mass Transfer Forced Convection Flow along a Vertical Stretching Sheet with Heat Generation and Radiation (Bangladesh Journal of Scientific and Industrial Research, 2011)
The present study comprises of steady two dimensional magnetohydrodynamic heat and mass transfer forced convection flow along a vertical stretching sheet in the presence of magnetic field with radiation. The nonlinear partial differential equations governing the flow field occurring in the problem have been transformed to dimensionless nonlinear ordinary differential equations by introducing suitably selected similarity variables. The ensuing equations are simultaneously solved by applying Nachtsheim-Swigert shooting iteration technique with sixth order Runge-Kutta integration scheme. The results in the form of velocity, temperature and concentration profiles are then displayed graphically. The corresponding skin-friction coefficient, Nusselt number and Sherwood number are displayed graphically and also in tabular form as well. Several important parameters such as the prandtl number (Pr), radiation parameter (N), magnetic field parameter (M), heat source parameter (Q), schmidt number (Sc), suction parameter (fw ) and eckert number (Ec) are confronted. The effects of these parameters on the velocity, temperature and concentration profiles are investigated. Key Words: MHD; Forced convection; Stretching sheet; Radiation; Heat generation. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8183 Bangladesh J. Sci. Ind. Res. 46(2), 169-176, 2011